Kejahatan Korporasi pada BUMN dan Implikasi Pertanggungjawaban Direksi: Analisis Kasus Pengadaan LNG Pertamina - Zainul Arifin; Ismi Lailatul Maulida; Rahayu Sri Utami (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study analyzes the corporate crime perspective and directors’ liability in the LNG procurement case at Pertamina as a State-Owned Enterprise (SOE). The research aims to examine how the elements of corporate crime are constructed, how directors’ actions are assessed within the framework of fiduciary duty and the business judgment rule, and what legal implications arise for corporate accountability in SOEs. The study employs a normative juridical method using a case approach, statute approach, and conceptual approach. Primary data consist of court documents, statutes, and regulatory frameworks, while secondary data are obtained from academic journals, institutional reports, and credible publications. The findings reveal that distinguishing legitimate business risk from abuse of authority is central to determining corporate criminal liability, particularly when decisions intersect with state finances and public interests. The analysis further indicates that SOE directors carry dual obligations: to ensure effective corporate governance while at the same time facing heightened exposure to criminal liability when losses are associated with state assets. This study contributes by clarifying how legal assessments should balance accountability with the protection of reasonable managerial discretion. The implications highlight the need for clearer decision-making standards, stronger governance mechanisms, and better alignment between corporate law and anti-corruption frameworks in order to promote legal certainty without discouraging prudent business judgment.